Emerging Elastic Micro-Nano Materials for Diagnosis and Treatment of Thrombosis - Chenxin Lu; Chunjian Li; Ning Gu; Fang Yang (Research)
Thrombus is a blood clot that forms in a blood vessel at the point of flaking. Thrombosis is closely associated with cardiovascular diseases caused by different sources and factors. However, the current clinical methods of thrombus diagnosis and treatment still have problems with targeting, permeability, stability, and biosafety. Therefore, in recent years, based on the development of micro/nano technology, researchers have tried to develop some new strategies for the diagnosis and treatment of thrombosis. Due to the unique structural characteristics, the micro-nano materials in physiological environments show excellent transport and delivery properties such as better in vivo circulation, longer life span, better targeting ability, and controllable cellular internalization. Especially, elasticity and stiffness are inherent mechanical properties of some well-designed micro-nano materials, which can make them better adapted to the needs of thrombosis diagnosis and treatment. Herein, this review first introduces the thrombotic microenvironment to characterize the thrombus development process. Then, to fine-tune the pathological occurrence and development of thrombosis, the role of elastic micro-nano materials for thrombus diagnosis and treatment is summarized. The properties, preparation methods, and biological fate of these materials have been discussed in detail. Following, the applications of elastic micro-nano materials in biomedical imaging, drug delivery, and therapy of thrombosis are highlighted. Last, the shortcomings and future design strategies of elastic micro-nano materials in diagnosis and treatment of clinical thrombosis are discussed. This review will provide new ideas for the use of nanotechnology in clinical diagnosis and treatment of thrombus in the future.